2023
DOI: 10.3390/bioengineering10060742
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Fat to Reverse Radiation Induced Soft Tissue Fibrosis

Abstract: Adipose tissue is composed of a collection of cells with valuable structural and regenerative function. Taken as an autologous graft, these cells can be used to address soft tissue defects and irregularities, while also providing a reparative effect on the surrounding tissues. Adipose-derived stem or stromal cells are primarily responsible for this regenerative effect through direct differentiation into native cells and via secretion of numerous growth factors and cytokines that stimulate angiogenesis and disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…These cells and the stromal vascular fraction (SVF) stimulate angiogenesis and disrupt pro-inflammatory pathways, offering a regenerative effect on the damaged tissues. 10…”
Section: Fat Graftingmentioning
confidence: 99%
“…These cells and the stromal vascular fraction (SVF) stimulate angiogenesis and disrupt pro-inflammatory pathways, offering a regenerative effect on the damaged tissues. 10…”
Section: Fat Graftingmentioning
confidence: 99%
“…Most importantly, ADSCs have been shown to increase vascular density in previously irradiated tissue fields. 46 While the exact mechanism by which these cells induce changes in the microvasculature remains unclear, studies have proposed that ADSCs orchestrate endothelial sprouting via secretion of proangiogenic factors such as VE growth factor. 47 Likewise, Nie et al 48 observed direct differentiation of ADSCs into angiogenic cell lineages to promote neovascularization.…”
Section: Future Perspectives For the Fieldmentioning
confidence: 99%
“…Although there are currently no specific therapeutics available to overcome it, the advent of cell-based therapies, notably augmentation of fat grafts with adipose-derived stromal cells (ADSCs), has shown promising results. Most importantly, ADSCs have been shown to increase vascular density in previously irradiated tissue fields 46 . While the exact mechanism by which these cells induce changes in the microvasculature remains unclear, studies have proposed that ADSCs orchestrate endothelial sprouting via secretion of proangiogenic factors such as VE growth factor 47 .…”
Section: Future Perspectives For the Fieldmentioning
confidence: 99%